Proximate composition and fatty acid profile of shabbout (Barbus grypus Heckel) caught from the Ataturk Dam Lake, Turkey - Gokce, Mahmut A.; Tasbozan, Oguz; Tabakoglu, S. Surhan; Celik, Mehmet; Ozcan, Filiz; Basusta, Asiye (Wfl Publ, 2011)
Shabbout (Bat-bus grypus;Cyprinidae) is an omnivorus, fast growing, highly appreciated and one of the main candidate fish species for aquaculture in the Tigris and Euphrates fluvial system. The nutritional quality of this wild species is still unknown and consequently this study was designed to investigate the proximal composition and fatty acid profile of Shabbout filet, and to note whether this species is suitable for fish farming in the area. Samples of two mature males and six females at different stages of maturity, obtained from local fishermen between May and June, were used in the study. Significant differences in proximate composition were observed among the samples, the moisture, ash, lipid and protein contents being 70.8 -76.1%, 1.4-2.4%, 2.0-5.3% and 15.0-21.6% wet weight, respectively. Variations in lipid content between genders were detected, with significantly higher lipid levels in males. Maturity stage of fish is considered one of the reasons for intra-specific variation in the proximate composition, especially in the case of lipids. Thus, the differences observed among shabbout females in the present study might be attributed to variations in the stage of maturity. Monounsaturated fatty acids (MUFA) were the highest fatty acid group followed by saturated (SFA) and polyunsaturated fatty acids (PUFA) in the flesh of all the samples. PUFA content of shabbout ranged between 19.2% and 26.1% being docosahexaenoic acid (DHA, C22:6 omega 3), linoleic acid (LA, C18:2 omega 6), eicosapentaenoic acid (EPA, C20:5 omega 3) and eicosatrienoic acid (C20:3 omega 3), the most important PUFAs. According to the present results in omega 3 series, shabbout is a good source for EPA and DHA as well as for the ratios omega 3/omega 6 (2.4-4.8) and omega 6/omega 3 (0.2-0.4) that were found to be within the recommended limits for human nutrition.
Keywords: Shabbout; Barbus grypus; proximate composition; fatty acid profile; SFA; PUFA; EPA; DHA